Produktivitas Organisasi Sekber PMVBI (Pemuda Buddhayana) Kabupaten Jepara Menurut Gaya Komunikasi Pemimpin - Okki Setiya Wijaya; Santi Paramita; Adi Nugroho Susanto Putro (Sekolah Tinggi Agama Buddha Nalanda, 2023)
According to (Oei et al., 2022), leadership communication style is very important for the productivity of an organization. Leadership is basically the ability that a person has to guide, nurture, and direct other people so that they can obey and work together to achieve the expected goals. According to Steward L.Tubbs and Sylvia Moss in (Ritonga & Islamy, 2019), there are six kinds of communication styles, namely The Controlling Style, The Equalitarium Style, The Structuring Style, The Dynamic Style, The Relinquishing Style, and The Withdrawal Style. This study aims to determine the productivity of PMVBI Secretariat Organization (Pemunda Buddhayana) in Jepara Regency based on leader communication. The sample data for this study took data from two leadership periods, the 2017-2020 and 2021-2024 leadership periods. The method used in this study is a qualitative research method, with a natural observation approach. The results of the study show that PMVBI Secretariat Organizational Leaders for the 2017-2020 period use the Withdrawal Style, Structural Style, Relinquishing Style, and Equalitarian Style of communication. Meanwhile, PMVBI Secretariat Organizational Leaders for the 2021-2024 period use the Structural Style, Relinquishing Style, and Equalitarian Style of communication. The application of the Withdrawal Style communication style causes the organization to experience inactivity. Meanwhile, Structural Style, Relinquishing Style, and Equalitarian Style make the organization more productive.